The impact of monetary and non-monetary incentives on employee’s motivation: a case of non-teaching staff of Kumasi Polytechnic. - Nkansah, Eunice (2017)
A thesis submitted to Department of Marketing and Corporate Strategy Kwame Nkrumah University of Science and Technology - School of Business in partial fulfilment of the requirements for the degree of Masters of Business Administration (Strategic Management option), School of Business, KNUST, College of Humanities and Social Sciences,